Neotypification of the name Atriplex pentandra (Amaranthaceae, Chenopodioideae) - Brignone, Nicolás F. (Phytotaxa, 2017)
Atriplex Linnaeus (1753: 1054) is a genus of about 260 species distributed in arid and semiarid regions of Eurasia, America and Australia (Sukhorukov & Danin 2009, Iamonico 2013, Brignone et al. 2016). Several names (at species, subspecies, variety and form ranks) were described related to the high phenotipic variability of this critical genus (IPNI 2008, Al-Turki et al. 2000). As conseguence, misapplication of names and nomenclatural disorders exist and need clarification (see e.g., Sukhorukov 2010, Iamonico 2012).